MECHANISMS IN THE SYNTHESIS OF FORSTERITE NANOPARTICLES BASED ON THERMODYNAMIC APPROACH - AVRAM, Alexandra; FLOREA, Diana Alexandra; GOGA, Firuța; GOREA, Maria; MOCANU, Aurora; TOMOAIA, Gheorghe; PETEAN, Ioan; KUN, Attila-Zsolt; HOROVITZ, Ossi; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2023)
Due to the ions in its structure, that have a variety of important roles in bone metabolism, forsterite (FS, Mg2SiO4) is a promising candidate for orthopedic and dental applications. This paper studies forsterite synthesized through two methods, namely sol-gel (FSsg) and precipitation (FSpp), based on a thermodynamic approach. Therefore, the precursor gel and precipitate were analyzed through thermal gravimetric (TG), differential thermal gravimetric (DTG) and differential scanning calorimetric (DSC) analysis. The FSsg and FSpp powders were characterized by X-ray powder diffraction (XRD) and atomic force microscopy (AFM). XRD reveals that the synthesized forsterite is of high crystallinity. As is evidenced by AFM, the average size of the nanoparticles is around 40 nm for FSsg and 30 nm for FSpp. The potential reaction mechanisms for the two synthesis routes were also established.